Study on the Dissolution Mechanism of Cellulose by ChCl-Based Deep Eutectic Solvents - Zhang, Heng (Materials (Basel), 2020)
Four deep eutectic solvents (DESs), namely, glycerol/chlorocholine (glycerol/ChCl), urea/ChCl, citric acid/ChCl, and oxalic acid/ChCl, were synthesized and their performance in the dissolution of cellulose was studied. The results showed that the melting point of the DESs varied with the proportion of the hydrogen bond donor material. The viscosity of the DESs changed considerably with the change in temperature; as the temperature increased, the viscosity decreased and the electrical conductivity increased. Oxalic acid/ChCl exhibited the best dissolution effects on cellulose. The microscopic morphology of cellulose was observed with a microscope. The solvent system effectively dissolved the cellulose, and the dissolution method of the oxalic acid/ChCl solvent on cellulose was preliminarily analyzed. The ChCl solvent formed new hydrogen bonds with the hydroxyl groups of the cellulose through its oxygen atom in the hydroxyl group and its nitrogen atom in the amino group. That is to say, after the deep eutectic melt formed an internal hydrogen bond, a large number of remaining ions formed a hydrogen bond with the hydroxyl groups of the cellulose, resulting in a great dissolution of the cellulose. Although the cellulose and regenerated cellulose had similar structures, the crystal form of cellulose changed from type I to type II.